The DNA barcodes for the species delimitation of the genus \(Tylopus\) Jeekel, 1968 in Vietnam (Diplopoda: Polydesmida: Paradoxosomatidae) - Anh, Nguyen Duc; Anh, Nguyen Thi Thu; Luong, Phung Thi Hong; Hoa, Dang Thi; Son, Nguyen Giang (Academia Journal of Biology, 2021)
The 680 bp fragment of the COI gene was employed for DNA barcodes of the millipede genus Tylopus in Vietnam. A total of 22 samples representing for 14 morphological Tylopus species were analyzed. The K2P genetic divergence between Tylopus species ranges from 12.2% to 18.9% with a mean of 15 ± 1%. The intraspecific divergences are slightly different between species, from 3% to 5%. The AGBD analysis and phylogenetic trees also support 14 morphological species. It is also suggested to have more COI sequences of more species for better barcode reference library and better molecular species identification.